Particle dynamics in subtropical and tropical Northeast Atlantic - Cruise No. MSM18/1 - April 14 - May 8, 2011 - Las Palmas (Spain) - Mindelo (Cape Verde) - Waniek, Joanna J; Fischer, Gerhard; Fründt, Birte; Thiede, Carl; Körner, Hans-Michael; Körner, Gerhard; Schmidt, Tino; Yakovlev, Sergey; Iversen, Morten; Ruhland, Götz; Basse, Andreas; Thiele, Stefan; et al. (DFG-Senatskommission für Ozeanographie, 2012)
In the Madeira Basin, our work concentrated on (1) the recovery of the Kiel276-27 mooring line after two years of deployment and the deployment of the Kiel276-28 for another 2 years and (2) intensive deep water trials with the newly developed ROV based on the DNS technology. Both sediments traps covering two years of particle flux and 6 current meters (Aanderaa) were successfully recovered, extending the existing data sets by another two years of records. In total the times series of currents at Kiel276 cover continuously 31 years (1980- 2011) and 18 years (1993-2011) of almost continuous sediment trap data are available. Initially the ROV trials were successful, and we were able to deploy the ROV in the vicinity of Kiel276 and had a first glance at the sea floor in the Madeira abyssal plain. However, technical problems with the wire connecting the TMS with the ROV led to a terminal loss of the ROV unit. In the NW African upwelling system and in the area of the Cape Verde Islands (TENATSO site), our second working area, almost all parts of the scheduled work were successfully done, even due to the late departure of the ship in Las Palmas. All sediment traps, including drifting and moored arrays were recovered and promising and complete samples sets were received. The annual sediment trap records provide, at first glance, rather low fluxes in the years 2010-11 off NW Africa, probably due to the negative NAO index. The drifting trap samples give indication of strong degradation of fecal pellets in the upper water column (<400 m). The systems deployed for sampling the water column worked perfectly, except the particle camera had some problems of recording pictures at a few sites. Nevertheless, we could find a prominent deep-water particle nepheloid layer off Cape Blanc applying the optical measurements. Unfortunately, we were unable to use the ROV system for the estimation of in situ particle settling speeds in the deeper water column. For the first time, we correlated the particle layers in the water column detected by optical systems with acoustic signals (PARASOUND and ADCPs). : MARIA S. MERIAN-Berichte